Two new species of Enderleina Jewett (Plecoptera: Perlidae) from northern Brazil - Hamada, Neusa; Da Silva, Jeferson Oliveira (Zootaxa, 2019)
Enderleina Jewett, 1960 is a small genus of Perlidae with seven species occurring in Venezuela and northern Brazil. Specimens deposited in the Invertebrate Collection of the Instituto Nacional de Pesquisas da Amazônia (INPA), Manaus, Brazil, identified formerly as E. flinti Stark, 1989 (n = 3) and E. yano Stark, 1989 (n = 6), were determined to represent three taxa, two of which are new species. Both new species were collected in Amazonas State, Brazil and are distinctive within the genus due to their unique adult color patterns. The third taxon is represented by a female similar to E. khazeni Derka & Tierno Figueroa, 2013, the male of which was described from the nearby Gran Sabana, Venezuela. However, since the female of this species is not known, the specific identity of this female cannot be assigned specifically with confidence. In this paper, we describe two new species of Enderleina from Brazil, clarifying the specific status of the Enderleina specimens in the collection of INPA, and correcting the geographical distributions of E. flinti and E. yano. There are no valid records of these two species for Brazil. Currently, four species of the genus are known from Brazil.